The Impact of Training Needs Assessment, Religiosity and Work Ethics on Job Performance at the Islamic Religious Department in Malaysia - Panji Hidayat bin Mazhisham (Universiti Sains Islam Malaysia, 2025)
Matric: 4150027 (FKP) _Restricted until Sept 2028